Molecular characterization of some closely related species of Utricularia L. using inter-SSR markers - Rahman, M Oliur; Kondo, Katsuhiko (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 11-20, 2003 (December)